The Third Rome : 1922-43 ; the making of the fascist capital - Kallis, Aristotle A. 1970- (Palgrave Macmillan, 2014)
"Rome underwent a spectacular transformation under Fascist rule; a transformation that was visual and topographical but also deeply symbolic. The 'third Rome' that Mussolini envisioned and sought to realise in the 1920s and 1930s was partly a new city, expanding in all directions from the historic centre, and partly a new vision for an ideal city that emerged from within a cityscape forged across millennia of history. This Rome was intended to be both the capital of a regenerated Italy and the sanctuary of a new international fascist political religion. Aristotle Kallis traces the plethora of visions and projects that sought to reimagine, reinvent, and reshape the city as a 'fascist capital' over the course of twenty short years. Extensive demolitions, reconfigurations of sites and monuments, as well as ambitious new constructions designed by an array of architects in wildly different styles, chronicle a fascinating story of conquering drive, ruthless appropriation, and interrupted ambition"--